ANALISA TINGKAT KEPUASAN PETANI PETERNAK KAMBING POTONG TERHADAP ASPEK AGRIBISNIS GAPOKTAN AGRO MANDIRI DI KECAMATAN PONGGOK KABUPATEN BLITAR - Oryza Septian Hananditya; Edya Moelia Moeis; Agustina Widyasworo (AVES: Jurnal Ilmu Peternakan, 2020)
The main reasons of this observations is to know how much satisfied beef goat farmers can got about combined farmer groups agricultural aspect that their settle on to fulfil their needed. This observations did on Ponggok Sub-District. Selecting the responden using surfeited sampling. Analysis method using method called IPA (Importance Performance Analysis) cartesius diagram and scoring system using likert scale method, and using index calculating or interval scoring from likert method to put final category in the end of analysis The answer from satisfied agricultural aspect analysis using likert method and IPA method cartesius diagram is. Using index calculating Ponggok Sub-District got 379 Point which means got standart high category. IPA method Ponggok Sub-District got 1 variable to work with that is affiliations mediators in farming service with outside group authority and 6 other variable can be increased or just stay still. The conclusions from the observations is, Ponggok Sub-District got standart high category and needed to increasing the affiliations in farming service with outside group authority variables